3.2k views
5 votes
X-y = -10 2x+4y=22 substitution

User Laurian
by
5.6k points

1 Answer

3 votes

Answer:

[1] x - 4y = 22

[2] 2x + 5y = -21

Explanation:

Solve equation [1] for the variable x

[1] x = 4y + 22

// Plug this in for variable x in equation [2]

[2] 2•(4y+22) + 5y = -21

[2] 13y = -65

// Solve equation [2] for the variable y

[2] 13y = - 65

[2] y = - 5

// By now we know this much :

x = 4y+22

y = -5

// Use the y value to solve for x

x = 4(-5)+22 = 2

I am sorry if I get it wrong.

User Daveen
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.